Assessing the agro-environmental efficiency from electricity production of BRICS countries using desirable and undesirable inputs : the enhanced DEA approach - Ndwambi, Tikanani (My University, 2023)
The Data Envelopment Analysis (DEA) is a well-established non-parametric methodology for evaluating the relative efficiency of a set of comparable entities called decision making units (DMUs) with multiple inputs and output. In existing studies that benchmarked energy, the DEA has been widely used to study and compare the efficiency of energy industries, particularly in the electricity industry. Agro-environmental efficiency, as adopted by this study, is the ability of using the desirable and undesirable inputs in the electricity production, minimize them to obtain the desirable outcome of outputs (GDP and Income per capita) through the increased agricultural production. Agro-environmental efficiency refers to a kind of efficiency that considers both the economic and the agro-environmental factors in a system. This paper proposes two methods of data envelopment analysis (DEA) approach to assess the environmental efficiency of electricity production in BRICS countries namely, Brazil, Russia, India, China, and South Africa using desirable and undesirable inputs. The study aimed at assessing the Agro-environmental efficiency from electricity production of BRICS countries using desirable and undesirable inputs. The study has three objectives which are to estimate the Agro-environmental efficiency of BRICS countries from electricity production using desirable inputs, to measure the Agro-environmental efficiency of the BRICS countries from electricity production using undesirable inputs and to determine socio-economic factors that affect Agro-environmental efficiency from electricity production of the BRICS countries using desirable and undesirable inputs. The Data Envelopment Analysis (DEA) results in method 1 showed that the Agri-environmental efficiency (AEE) scores of the states in the BRICS countries had a mean of 47.12% with a minimum of 10% and a maximum of 100%. The implications are that BRICS countries were Agro-environmental inefficient on average. The use of the undesirable inputs should be minimized, as well as the undesirable outputs on average by approximately 52.88% and maximize the use of desirable inputs to obtain the same output level. The Agro-environmental efficiency scores in method 2 showed that the states of the BRICS countries had a mean of 54.06% with a minimum of 1% and a maximum of 100%. The AEE score in this method shows that the states in the BRICS countries are ii Agro-environmental inefficient. This implies that states are not minimizing undesirable inputs fully (Methane and CO2) to maximize the use of desirable inputs (Coal, diesel, and Gasoline) in electricity generation. The undesirable inputs in the electricity production could be decreased by approximately 45.94% on average to obtain the same level of output. The study also found that socioeconomic factors attributed to Agro-environmental efficiency in the BRICS countries were population, an agricultural area, industrial area, and rapid urbanisation. The population is significant towards the Agro-environmental efficiency of the BRICS countries at 5% significance level with a positive coefficient of 2.013. the agricultural area was found to positively influence Agro-environmental efficiency at a 1% significance level with a positive coefficient of 1.052. The industrial area was found to have the negative relationship with the Agro-environmental efficiency with a significance level at 10% and a coefficient of -2.001. the rapid urbanisation is significant towards the Agro-environmental efficiency at 5% significance level with a positive coefficient of 1.082. The study recommends the measures to improve efficiency in the electricity production in the BRICS countries. Such measure amongst others are to allow ecosystems to adapt naturally to climate change, ensure that food production is not threatened, and to enable economic development to proceed in a sustainable manner.
Thesis (M.Sc. (Agricultural Economics)) -- University of Limpopo, 2023
Keywords: Agro-environmental efficiency; Data envelopment analysis; BRICS states; Electricity in agriculture; Electric power production; Data envelopment analysis